Innovation of Balsa Wood Topical Steroids Applicator in Psoriasis Patients: Advanced Practice Nurse’s Roles - Tangpradit, Yuwapat; Yodchai, Kantaporn (Journal of Research in Nursing-Midwifery and Health Sciences, 2023)
Introduction: Design thinking is a thinking process that involves a deeper understanding of problems with a user-centered approach. It brings creativity and various perspectives to develop a solution to the problem. In this paper, the authors present the concept of applying design thinking in advanced practice nurse’s roles (community nursing) for developing the nursing innovation “balsa wood topical steroids applicator in psoriasis patients.” Design thinking includes a five-step process: (1) empathize (2) define (3) ideate (4) prototype and (5) test. There were three prototype developments, of which the 3rd design was tested in 30 patients with psoriasis. The study found that the incidence of side effects from steroid application was 0% and the overall satisfaction level was 89.70%. In addition, in terms of the satisfaction with each aspect, it was found that the innovation: (1) enabled medicine to be well absorbed into the skin rash, reducing drug loss by 83%. In addition, it was: (2) light weight and easy to carry by 100%, (3) a suitable size, easy to use by 98%, (4) easy to clean and maintain by 96%, and (5) a product that prevents contamination of the medication in the cartridge by 90%. Conclusion: Development of the balsa wood topical steroids applicator innovation applied the design thinking method to solve problems and develop new ideas in order to solve psoriasis patient’s problems effectively.